Perkembangan Penyakit Busuk Batang pada Kelapa Sawit Pasca Peremajaan Tanaman - Hutagaol, Paulus; Wirianata, Herry; Kristalisasi, E. Nanik (Jurnal Agro Industri Perkebunan, 2024)
Basal stem rot caused by the fungus Ganoderma boninense is the major threat to oil palm plantations in Indonesia, especially for second generation. Handling oil palm residues during the replanting process greatly determines the fungal attack. This research aims to reveal how handling oil palm trunks affects G. boninense attacks on second generation oil palm plantations. The treatments studied were felled trunk and felled-chipped trunk, each represented by two blocks (five years old of oil palm) with a density of 143 trees/hectare. The results of the study showed that second generation oil palms had a very high prevalence of basal stem rot disease, even though there were differences in the incidence and severity of the disease. Chipping of felled trunk residues can slow the development of the disease. Management of palm residues has a major influence on the onset of this disease in replanted oil palms.